The Feasibility of Saga Text Teaching Materials Utilizing a Website for Assignments and Resources in Class X at Azizi Islamic Senior High School - Muhammad Zulfadlan Nduru; Ali Ali; Rita Rita (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to develop, assess the feasibility, and evaluate the effectiveness of saga text teaching materials utilizing a website as a platform for assignments and resources for Class X students at Azizi Islamic Senior High School. Methodology: This study employs a Research and Development (R&D) approach using the 4D model by Thiagarajan, consisting of Define, Design, Development, and Dissemination stages. The research methods include qualitative and quantitative approaches. Data were collected through observations, interviews, and questionnaires, with material experts, media experts, teachers, and students serving as evaluators. The study uses a saturated sampling technique, involving 18 students from Class X. Main Findings: The feasibility assessment categorized the saga text teaching materials as